Política e trabalho pedagógico da EJA EPT: olhares sobre o Curso Técnico em Cozinha do Instituto Federal Farroupilha Campus São Borja – RS - Gusmão, Martina Bernabeth Isnardo (2021)
This dissertation is part of the work and education theme, in the Research and Management Policy Line in Professional and Technological Education of the Graduate Program in Professional Education of the Colégio Técnico Industrial de Santa Maria - CTISM. This research has as general objective to analyze the policies of EJA EPT and the pedagogical work in the Technical Course in Kitchen of the Federal Farroupilha Institute, Campus of São Borja - RS, from the students' speeches. The specific objectives are as follows: to contextualize the trajectory of the Vocational Education Integrated to High School policy in the Youth and Adult Education modality; to know the historicity of the policy and the characteristics of EJA EPT students from the Technical Course in Cooking at the Federal Farroupilha Institute, São Borja campus; identify, from the students' speeches, how the EJA EPT policy and pedagogical work on campus materialize. It is a research with a qualitative approach and its instruments for the production of data are documentary analyzes, the application of questionnaires and the realization of a focus group. The analyzes were organized based on the content analysis of Bardin (2011). The main theoretical references are Manfredi (2016), Marx (2013), Konder (2004), Saviani (2007), Ferreira (2010 and 2018), Maraschin (2015 and 2019), Vieira Pinto (2010/2017), Ciavatta (2019), Frigotto (2012), Bardin (2011), Arroyo (2017). The results demonstrate that the TP contributes to the formation of critical subjects and committed to social development, but the world of work in the municipality tends to precarious the professional Kitchen Technician. From these findings by the students' speeches, actions are suggested for the management of the IF to reformulate the course and practices, and actions for the municipal management in order to value technical and higher education in the world of work in São Borja – RS.